Indoor volatile organic compounds exposures and risk of childhood acute leukemia: a case-control study in shanghai. Issue 2 (12th December 2020) - Zhang, Yan; Chen, Didi; Shi, Rong; Kamijima, Michihiro; Sakai, Kiyoshi; Tian, Ying; Gao, Yu
Abstract: A case-control study was conducted to investigate the relationship between indoor air pollution and childhood acute leukemia (AL) in Shanghai. 97 cases and 148 gender-, age-, and residence-matched controls were included. Indoor air pollution was evaluated by questionnaires and quantitative measurement including 14 volatile organic compounds (VOCs) and nitrogen dioxide (NO2 ) in the homes of the two groups. The levels of individual VOCs, VOC families, TVOC (sum of the concentrations of the individual VOCs) and NO2 were compared between the two groups. Exposure to styrene and butyl alcohol were associated with an increased risk of childhood AL (styrene: odds ratio ( OR) =2.33, 95% confidence interval ( CI) : 1.07-5.07; butyl alcohol: OR  = 2.51, 95% CI : 1.19-5.28); 4th quartile of chlorinated hydrocarbons ( OR  = 2.52, 95% CI: 1.02-6.26) and 3rd quartile of TVOC ( OR  = 4.03, 95% CI: 1.06-6.81) had significant higher OR s for childhood AL compared with that in the lowest quartiles. Elevated levels of individual VOCs, VOC families and TVOC were also associated with self-reported risk factors. Our findings suggest that VOCs exposure was associated with an elevated risk of childhood AL, underscore that more attention should be paid to indoor air pollution as a risk factor of childhood AL.